LEKSIKON AMAIK DALAM RITUAL NAAH PADI PADA MASYARAKAT DAYAK SALAKO DI KECAMATAN SAJINGAN BESAR SAMBAS - Iyon, Firminus; Amir, Amriani; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â Abstract Amazon's lexicon of rice is a component of language communication Â that contains the meaning and usage of words in the language. Amaik rice is the rule of things prohibited and abstinent in the form of speech and action in rice farming activities. This is the reason the researchers chose amaik rice in Dayak Salako language. The wisdom of the Dayak Salako rice field traditions is a distinct characteristic of the other Dayak sub-groups. Rice is considered a sacred object that has a spirit that should be given special treatment through traditional ritual traditions. Amaik rice contains a meaning that has cultural aspects and culture of the culture owner's community. So amaik rice is maintained. Dayak Salako is one of the Dayak sub-villages area in Sajingan sub-district Sambas District. The research was conducted in Sasak village of Santaban village, Sajingan Besar sub-district of Sambas district, which is a residential area of indigenous Dayak Salako community. This study includes rice amaik's speech, lexicon form amaik rice, and cultural sense amaik rice.Â Keywords: lexicon, Amaik, Dayak Salako